Child martyrs and militant evangelization in New Spain: missionary narratives, Nahua perspectives - Schmidt, Stephanie (The William & Bettye Nowlin series in art, history, and culture of the western hemisphere, 2024)
"A cornerstone of the evangelization of early New Spain was the conversion of Nahua boys, especially the children of elites. They were to be emissaries between Nahua society and foreign missionaries, hastening the transmission of the gospel. Under the tutelage of Franciscan friars, the boys also learned to act with militant zeal. They sermonized and smashed sacred objects. Some went so far as to kill a Nahua religious leader. For three boys from Tlaxcala, the reprisals were just as deadly. In Child Martyrs and Militant Evangelization in New Spain, Stephanie Schmidt sheds light on a rare manuscript about Nahua child converts who were killed for acts of zealotry during the late 1520s. This is the Nahuatl version of an account by an early missionary-friar, Toribio de Benavente Motolinía. To this day, Catholics venerate the slain boys as Christian martyrs who suffered for their piety. Yet Franciscan accounts of the boys' sacrifice were influenced by ulterior motives, as the friars sought to deflect attention from their missteps in New Spain. Illuminating Nahua perspectives on this story and period, Schmidt leaves no doubt as to who drove this violence as she dramatically expands the knowledge base available to students of colonial Latin America"-- Provided by publisher